A stomatin and a degenerin interact to control anesthetic sensitivity in Caenorhabditis elegans. - Rajaram, S (1999)
The mechanism of action of volatile anesthetics is unknown. In Caenorhabditis elegans, mutations in the gene unc-1 alter anesthetic sensitivity. The protein UNC-1 is a close homologue of the mammalian protein stomatin. Mammalian stomatin is thought to interact with an as-yet-unknown ion channel to control sodium flux. Using both reporter constructs and translational fusion constructs for UNC-1 and green fluorescent protein (GFP), we have shown that UNC-1 is expressed primarily within the nervous system. The expression pattern of UNC-1 is similar to that of UNC-8, a sodium channel homologue. We examined the interaction of multiple alleles of unc-1 and unc-8 with each other and with other genes affecting anesthetic sensitivity. The data indicate that the protein products of these genes interact, and that an UNC-1/UNC-8 complex is a possible anesthetic target. We propose that membrane-associated protein complexes may represent a general target for volatile anesthetics.